KONTRIBUSI LINGUISTIK PEDAGOGIS DALAM PEMBENAHAN MUTU PEMBELAJARAN BAHASA ARAB - Dinni Masyitoh Lindrianawati (Universitas Islam Negeri Mataram, 2021)
This paper aims to provide insight to all learners, researchers, andpractitioners in the field of Arabic, especially Arabic language teachers, asa final project of pedagogical linguistics. The number of Arabic learningproblems that occur in the field is due to several reasons, it can affect thequality of learning Arabic in schools. Therefore, pedagogical linguisticscontributes to providing several notes as a solution to improving the qualityof learning Arabic in schools, one of which is fixing the syllabus of learningoperations. The method used in this paper is literature study, namely bycollecting various literatures on pedagogical linguistics and literature onthe quality of Arabic learning, which the authors then synthesize so that itbecomes one of the solutions for improving the quality of Arabic learning inschools to make it even better.